Physical Properties and Compressive Strength of Pressed and Cast Fly Ash Geopolymer - L. Jia-Ni; L. Yun-Ming; M.M.A.B. Abdullah; T. Hoe-Woon; H. Yong-Jie; O. Shee-Ween; O. Wan-En (Archives of Metallurgy and Materials)
Geopolymers are commonly recognized as sustainable alternatives to OPC and it has broad range of applications. Certain properties of geopolymer such as density are concerned in order to apply in the construction industry. Different densities of geopolymer could be obtained by varying the concentration of the alkaline activator. However, the densities do not differ much. Hence, a different production method of geopolymer can be applied. This study aimed to investigate the physical properties and compressive strength of pressed and cast fly ash geopolymer. The geopolymer samples were prepared by using pressing and casting method. Geopolymer samples without foam addition and with foam addition were prepared in order to achieve different densities of samples. The results demonstrated that the pressed sample has the highest bulk density (2285 kg/m3) whereas the cast sample with added highest ratio of foam has the lowest bulk density (1293 kg/m3). The apparent porosity and water absorption result were inversely proportional to the bulk density result. The densest geopolymer obtained the highest compressive strength (61 MPa) and the lightest geopolymer obtained the lowest compressive strength (7 MPa).